EFEKTIFITAS TANAMAN SAGE (SALVIA) UNTUK MENURUNKAN GEJALA HOT FLASHESPADA WANITA MENOPAUSE - Bela Purnama Dewi; Jusnila Wati (Jurnal Kesehatan dan Pembangunan, 2026)
Menopause is a natural phase in a woman's life that is often accompanied by various symptoms, one of the most common being hot flashes—a sudden sensation of heat followed by excessive sweating. These symptoms can significantly impact women's quality of life. Due to concerns over the side effects of hormone therapy, the use of herbal treatments such as Salvia officinalis (sage) is being considered as an alternative remedy. This study aimed to determine the effectiveness of sage (Salvia officinalis) in reducing hot flash symptoms in menopausal women. This research employed a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 60 menopausal women experiencing hot flashes, selected through purposive sampling at Puskesmas Plaju Palembang. The intervention involved administering a sage infusion (100 grams in 200 ml of water), consumed once daily for seven days. Hot flash symptoms were measured before and after the intervention using a hot flash instrument. The data were analyzed using a paired sample t-test. The results showed that the administration of sage infusion was significantly effective in reducing hot flash symptoms in menopausal women, indicating that sage can serve as a safe and natural non-hormonal therapy alternative.